Impact of Service Environment for effective consumer behavior in Retails Industry with reference to Heritage Super Market - et.al, Mr. L Komagan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Consumer behavior is dynamic and it needs to be evaluated by using scientific research methods. In this regard market research for Heritage had been conducted in this research work. Consumer behavior is complex subject and it is tough to predict the human internal thinking unless they express their opinions. Customers are sometimes loyal to the existing brands and some customers always show interest to adopt disruptive technology. Retailing business is more traditional in India and it had transformed in the past once decade. At the same time consumption also increased with growth of organized retailing business in India. The survey was conducted in selected Heritage super markets and parlous in Hyderabad. It was descriptive research & Quantity research type and the samples were collect through convincing samples & Simple random samples. The hypothesis was tested using the Correlations, Regression and ANOVA testing. There was a significant effect on the service environment and consumer behavior in the retail market.